A novel use of hill function and utility of 99mTc-MIBI scintigraphy to detect earlier lower extremity microvascular perfusion in patients with type 2 diabetes. Issue 38 (September 2017) - Li, Yingsha; Li, Qiang; Liang, Shenju; Liang, Xia; Zhou, Wen; He, Hongbo; Jin, Rongbing; Wang, Kaifa; Zhu, Zhiming; Yan, Zhencheng
Abstract : Abstract: We use the Hill function to analyze the dynamics of Tc-99m 2 methoxy-isobutyl-isonitrile ( 99m Tc-MIBI) scintigraphy data and to examine the earlier lower extremity microvascular perfusion of diabetic patients without typical clinical symptoms and with the preserved normal ankle-brachial index (ABI). Eighty-eight participants (30 healthy control, 34 diabetic patients, and 24 diabetic patients with peripheral arterial disease [PAD]) were recruited and applied 99m Tc-MIBI scintigraphy. Fourteen diabetic patients with PAD also underwent computed tomography angiography (CTA) examination and were performed endovascular interventions. Diabetic patients with normal ABI already have significantly impaired maximum 99m Tc-MIBI muscle perfusion counts ( P < .001) and the peak times of the lower extremity muscle perfusion ( P < .05). 99m Tc-MIBI scintigraphy showed great consistent with ABI and CTA in detecting PAD. 99m Tc-MIBI scintigraphy was also found to be effective in evaluating lower extremity circulation after endovascular interventions ( P < .05). Hill function-based analysis of 99m Tc-MIBI scintigraphy might be effective method to evaluate earlier lower extremity perfusion changes in diabetic patients.